The Evolution of Generalised and Acute Job Tenure Insecurity. (August 2020) - Choonara, Joseph
An earlier article by Gallie, Felstead, Green and Inanc demonstrates that employee insecurity can be divided into job tenure insecurity (anxieties about the continuity of employment) and job status insecurity (anxieties about the loss of valued features of the job). Here it is argued that job tenure insecurity can be further divided into acute and generalised variants. The former tracks the level of involuntary redundancies in the UK data and is grounded in a realistic assessment of the likelihood of involuntary job loss. The latter is driven by a range of factors, including the economic cycle and the intensification of work that is also associated with rising job status insecurity, and the permeation of insecurity through new sections of the workforce. Its greatest extent was in the mid-1990s and it rose again in the years following the 2008/2009 recession.